(untitled) (Third Sector Social Economic Review, 2018)
Financial investors, producers and holders are exposed to some risks becouse of the fluctuations in economy. Persons and institutions seeking to protect themselves from the risks they face in the market are also turning to futures markets for effective risk management and trying to minimize their risks. Futures markets are markets where any commodity or financial instrument is traded in the near future for delivery or cash settlement on a certain date. The price of the contractual asset is determined and fixed today. The securities that are traded on the futures markets are futures contracts. Futures contracts are forward, futures, option and swap contract types.